The effect of custom-fitted compression garments worn overnight for recovery from judo training in elite athletes - Brown, F. C. W.; Hill, J. A.; van Someren, K.; Howatson, G.; Pedlar, C. R. (European Journal of Sport Science, 2022)
This study investigated the effects of custom-fitted compression garments (CG) worn during recovery over a multi-day training camp in elite judo players (judoka). A single blind, placebo-controlled study was carried out in 11 elite judoka, using a two-way crossover design. Two three-day training camps were completed in CG and placebo conditions in a random order. Changes in performance and physiological markers were compared between conditions. Judoka were assessed before training for (maximal) isometric knee extension and grip strength, countermovement jump performance and bench-press velocity, alongside soreness, limb circumferences, plasma creatine kinase activity (CK) and perceived bruising. Measurements were repeated after 12, 36 and 43 h of training, whereupon judoka rated the effectiveness of each intervention. Knee extension and bench-press performance demonstrated significant familiarization (p < 0.001), and were excluded from subsequent analysis. Jump performance was unaffected by training (p > 0.05). Grip strength declined throughout training (p < 0.001), with peak decrements of -9.7% indicating mild muscle damage. Increases in bruising, CK and soreness demonstrated highly variable, if significant (p < 0.001) responses. Although CG were perceived as significantly more effective than placebo for recovery (p = 0.046), no effects were observed for any other outcome (p > 0.05). Compression conferred no statistically significant impact upon recovery markers in elite judoka throughout training. Muscle damage responses were inconsistent in this population. Individual athletes would be advised to monitor habitually-used performance measures while using CG to ascertain whether perceptual benefits translate into enhanced recovery.